Cardiovascular disease risk in middle-aged ultra-endurance athletes - Bachman, Nate P., author; Dinenno, Frank, advisor; Richards, Jennifer, advisor; Chicco, Adam, committee member; Orton, Christopher, committee member (Colorado State University. Libraries, 2018)
Background: It is widely accepted that aerobic exercise has the ability to reduce cardiovascular disease (CVD) risk. However, recent studies suggest that volumes of exercise that greatly exceed physical activity guidelines may be damaging to the heart. Currently, it is unclear if individuals who train for ultra-endurance races are at an elevated risk of developing CVD compared to those that perform lower amounts of physical activity. Purpose: To use traditional and novel measures of CVD risk to determine if individuals that train for ultra-endurance races have a greater CVD risk compared to participants that engage in recreational physical activity. Methods: We studied two groups of healthy, middle-aged adults (40-65 y); Control (CON, n=18) subjects included individuals who were meeting current physical activity guidelines and the athletes (ATH, n=25) had been training for ultra-endurance events for 10 years. We used cardiac computed tomography (CT) to calculate coronary artery calcium scores (CACS) and magnetic resonance imaging (MRI) to assess for myocardial fibrosis (MF). Vascular function was evaluated using carotid-femoral pulse wave velocity (cfPWA) and flow-mediated dilation (FMD). 10-Year coronary heart disease (CHD) risk was also determined using a risk score calculator. Results: CACS > 0 was observed in 2 CON and 8 ATH; however, the presence of CAC was not significantly different between groups (P>0.05). Additionally, no participants in CON or ATH had MF. CON had higher cfPWV compared to ATH (6.9±0.2 vs 6.2±0.2 m/s, P<0.05), while no differences in FMD were observed (CON; 5.6±1.2 vs ATH; 3.6±0.8 %, P>0.05). Furthermore, there were no group differences in CHD risk (CON; 1.6±0.3 vs ATH; 2.4±0.6 %, P>0.05). Conclusion: ATH training for ultra-endurance races are not at a greater risk of experiencing a cardiac event than individuals that meeting current physical activity guidelines.